1998
DOI: 10.1152/ajpregu.1998.275.4.r1343
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for increased cardiac compliance during exposure to simulated microgravity

Abstract: We measured hemodynamic responses during 4 days of head-down tilt (HDT) and during graded lower body negative pressure (LBNP) in invasively instrumented rhesus monkeys to test the hypotheses that exposure to simulated microgravity increases cardiac compliance and that decreased stroke volume, cardiac output, and orthostatic tolerance are associated with reduced left ventricular peak dP/d t. Six monkeys underwent two 4-day (96 h) experimental conditions separated by 9 days of ambulatory activities in a crossove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Surprisingly, cardiac output did not decrease. Several hypotheses have been suggested, which include thoracic (Foldager et al 1996) and cardiac (Koenig et al 1998) biomechanical changes that are specific to real conditions of weightlessness. During weightlessness, the chest relaxes and thus the volume of the closed chest cavity increases.…”
Section: Fluid-electrolyte and Cardiovascular Changesmentioning
confidence: 99%
“…Surprisingly, cardiac output did not decrease. Several hypotheses have been suggested, which include thoracic (Foldager et al 1996) and cardiac (Koenig et al 1998) biomechanical changes that are specific to real conditions of weightlessness. During weightlessness, the chest relaxes and thus the volume of the closed chest cavity increases.…”
Section: Fluid-electrolyte and Cardiovascular Changesmentioning
confidence: 99%
“…Our previous work (52,55) showed the nature and time course of depression in contractility of papillary muscle of rats subjected to 4 and 13 wk of tail suspension. Koenig et al (25) demonstrated with invasively instrumented rhesus monkeys that, after 4 days of exposure to head-down tilt, the reduced orthostatic tolerance during graded lower body negative pressure was associated with a lowered Values are means Ϯ SE; n, number of animals. CSA, cross-sectional area of papillary muscle.…”
Section: Effectiveness Of Daily Short-duration ϫG X Exposure By Std Imentioning
confidence: 99%
“…The absence of gravitational stimuli during spaceflight induces a number of adaptive changes within the cardiovascular system that might affect crew health and safety, especially upon return to Earth (2,36). Most imperative, cardiovascular modifications occurring in microgravity consist of altered blood volume distribution (26,48), impaired myocardial properties (13,24,32), and/or end-organ (i.e., vascular) remodeling (11,39,49). In addition, the baroreflex in space is chronically unchallenged due to removal of intravascular hydrostatic pressure gradients.…”
mentioning
confidence: 99%